2023
DOI: 10.1097/hc9.0000000000000076
|View full text |Cite
|
Sign up to set email alerts
|

Copper deficiency is an independent risk factor for mortality in patients with advanced liver disease

Abstract: Background and Aim: Copper is an essential trace metal serving as a cofactor in innate immunity, metabolism, and iron transport. We hypothesize that copper deficiency may influence survival in patients with cirrhosis through these pathways. Methods: We performed a retrospective cohort study involving 183 consecutive patients with cirrhosis or portal hypertension. Copper from blood and liver tissues was measured using inductively coupled plasma mass spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…Copper plays an essential cofactor in innate immunity and metabolism. Previous studies have demonstrated that copper deficiency is an independent risk factor for mortality in patients with advanced liver disease ( 41 ). Moreover, another study revealed that although copper levels are elevated in various liver fibrosis conditions, severe copper deficiency induced by tetrathiomolybdate exacerbates liver injury and fibrosis in rats ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Copper plays an essential cofactor in innate immunity and metabolism. Previous studies have demonstrated that copper deficiency is an independent risk factor for mortality in patients with advanced liver disease ( 41 ). Moreover, another study revealed that although copper levels are elevated in various liver fibrosis conditions, severe copper deficiency induced by tetrathiomolybdate exacerbates liver injury and fibrosis in rats ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another of these liver diseases is acute-on-chronic liver failure, where the presence of an enlarged and unstable iron pool correlates with early mortality [43]. Moreover, copper deficiency is a recently discovered risk factor for infections and death before liver transplantation in patients with cirrhosis or portal hypertension [44]. In addition to lowering the CP acticity, copper deficiency reduces superoxide generation in neutrophils and macrophages, which directly impedes their bactericidal activity.…”
Section: And Copper Deficiency Disordersmentioning
confidence: 99%
“…Copper deficiency exacerbates hepatic fibrosis in bile duct-ligated rats, possibly mediated through reduced antioxidant defense and iron overload [15]. Notably, copper deficiency is relatively common in advanced cirrhosis and is associated with an increased risk of infection, a unique metabolic profile, and an increased risk of death before transplantation [16]. In addition, sugar intake further promotes the development of MASLD.…”
Section: Introductionmentioning
confidence: 99%